PENGARUH MEDIA SOSIAL TIKTOK DAN FOMO TERHADAP KEPUTUSAN PEMBELIAN MIE GACOAN YANG DIMEDIASI OLEH E-WOM PADA GENERASI Z DI KOTA PALANGKA RAYA - Listiawati Listiawati; Noorjaya Nahan; Peridawaty Peridawaty; Aston Pakpahan (LPPM STIE Muhammadiah Bandung, 2026)
The development of social media has transformed consumer behavior, particularly among Generation Z, in the purchase decision-making process. TikTok social media and Fear of Missing Out (FOMO) have become influential factors driving purchase decisions through exposure to digital content and interactions among users. This study aims to analyze the influence of TikTok social media and FOMO on purchase decisions of Mie Gacoan among Generation Z in Palangka Raya City, with Electronic Word-of-Mouth (E-WOM) as a mediating variable. This research employs a quantitative approach using a survey method with 100 respondents selected through purposive sampling. Data analysis was conducted using Structural Equation Modeling based on Partial Least Squares (PLS-SEM). The results indicate that TikTok social media has a positive and significant effect on purchase decisions, both directly and indirectly through E-WOM. FOMO does not have a significant direct effect on purchase decisions but has a significant indirect effect through E-WOM. Furthermore, E-WOM is proven to have a positive and significant effect on purchase decisions. Mediation testing reveals that E-WOM acts as a partial mediator in the relationship between TikTok social media and purchase decisions, and as a full mediator in the relationship between FOMO and purchase decisions. This study concludes that E-WOM plays a crucial role in shaping purchase decisions among Generation Z.